Pengaruh Motivasi Kerja dan Stres Kerja terhadap Kinerja Karyawan Bagian SPG PT.XYZ di Jawa Barat - Ruswandi, Anthy Febrianti; Aam Rachmat Mulyana (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effect of work motivation and work stress on employee performance at PT XYZ West Java. The research method used is a quantitative approach with descriptive and associative design. Data were collected by distributing questionnaires to 34 respondents who are the total population of company employees. Data analysis was carried out using validity, reliability, and multiple linear regression tests with the help of SPSS 25. The results of the study showed that work motivation has a positive effect on employee performance, while work stress has a negative effect. Simultaneously, these two variables have a significant effect on employee performance, with an R-Square value of 33.6%. The conclusion of this study is that increasing work motivation and good work stress management can improve employee performance at PT XYZ West Java.  Keywords: Work Motivation, Work Stress, Employee Performance, PT XYZ